Neospora caninum in birds : Review - Ali, Ayoub Ibrahim; Ahmed, Sabea Khamiss Abid; Najim, Thaar Mohammed; Hasan, Mustafa Salah (International Journal of Psychosocial Rehabilitation, 2020)
Neospora caninum belong to apicomplexan, cyst formation and intracellular parasite. Canids are definitive host for this parasite and the intermediate host include different species of domestic and wild animals and also birds. The parasite cosmopolitan in distribution and can causes economic losses in cattle. The birds that get the food from the earth may be ingested the N. caninum oocysts that shedding with the faeces of dogs and contribute to parasite dissemination. Presence the birds in the dairy cattle pastures result in reproductive problems of cattle. Although the effect of birds in the epidemiology of Neospora caninum is unknown, This review is cared on the Famous knowledge of neosporosis in birds.